2021
DOI: 10.1161/circulationaha.121.054083
|View full text |Cite
|
Sign up to set email alerts
|

Variant Intronic Enhancer Controls SCN10A-short Expression and Heart Conduction

Abstract: Background: Genetic variants in SCN10A , encoding the neural voltage-gated sodium channel NaV1.8, are strongly associated with atrial fibrillation, Brugada syndrome, cardiac conduction velocities and heart rate. The cardiac function of SCN10A has not been resolved, however, and diverging mechanisms have been proposed. Here, we investigated the cardiac expression of SCN10A and the function of a variant-sensitive intronic enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…The alternative exon usage of human CACNA1I and CACNA1H as well as mouse Cacna1f in T cells we demonstrate here has not been reported before. Of note, Man et al recently reported that human and mouse cardiomyocytes do not express full-length transcripts of the neuronal voltage-gated sodium channel Nav1.8 ( Scn10a ), but instead express a short transcript ( Scn10a-short ) comprising only the last 7 exons 76 . Transcription of this short variant occurred from an intronic enhancer-promoter complex.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative exon usage of human CACNA1I and CACNA1H as well as mouse Cacna1f in T cells we demonstrate here has not been reported before. Of note, Man et al recently reported that human and mouse cardiomyocytes do not express full-length transcripts of the neuronal voltage-gated sodium channel Nav1.8 ( Scn10a ), but instead express a short transcript ( Scn10a-short ) comprising only the last 7 exons 76 . Transcription of this short variant occurred from an intronic enhancer-promoter complex.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, although the expert panel did not identify SCN10A as a causative mutation of CPVT, SCN10A variants were reported in patients with multiple mutations, in addition to patients with BrS [ 52 , 95 ]. Basic studies have also shown that SCN10A variants affect the myocardial sodium current and therefore affect the arrhythmogenic susceptibility of the patient [ 96 , 97 ]. As the SCN10A variant has not been previously detected in a CPVT patient, further study is needed to elucidate the complex causative relationship between genetic mutations and the CPVT phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes have been implicated in BrS, although they remain disputed for diagnostic purposes (table 1). 29 SCN10A encodes a neuronal sodium channel pore subunit Na V 1.8 with expression in intracardiac neuronal tissue, and possibly cardiomyocytes 30. A common variant with loss of function has been associated with BrS 31.…”
Section: Introductionmentioning
confidence: 99%
“…A common variant with loss of function has been associated with BrS 31. Mechanistic effects of SCN10A variants could, however, be related to consequent altered expression of SCN5A, or altered expression of a Na V 1.5-interacting shortened SCN10A transcript protein Na V 1.8-short 30…”
Section: Introductionmentioning
confidence: 99%